Voltammetric Determination of Ophthalmic Drug Dexamethasone Using Poly-glycine Multi Walled Carbon Nanotubes Modified Paste Electrode - Demir, Ersin; Inam, Onur; Inam, Recai; Aboul-Enein, Hassan Y. (Current Analytical Chemistry, 2018)
Background: Dexamethasone has been used in ophthalmology for the treatment of different eye diseases and it is a powerful synthetic member of the glucocorticoid class of steroid medicament having anti-inflammatory and immunosuppressant characteristics. The aim of this study is to develop a rapid, sensitive and selective voltammetric method for its determination using polygylcine-multi walled carbon nanotubes (polyglycine-MWCNTs) modified paste electrode. Methods: The electro-activity and the voltammetric behavior of dexamethasone on the polyglycine- MWCNTs electrode were deduced by cyclic voltammetry (CV), square wave stripping voltammetry (SWSV), differential pulse voltammetry (DPV) and linear sweep voltammetry (LSV). The method permits accurate and sensitive detection of the ophthalmic drug dexamethasone in the presence of ascorbic acid, dopamine and uric acid from the generated anodic peaks at +950 mV, +740 mV and +700 mV, respectively. Results: The cyclic voltammetric study indicates that dexamethasone created a single anodic peak at about +1100 mV in pH 3 B-R solution and none of the cathodic peak appeared in the subsequent reverse scan. The detection and quantification limits measured for LSV were 0.087 mg/L and 0.29 mg/L, respectively. The extent of recoveries in the presence of equal amounts (1:1 mass ratio) of ascorbic acid, dopamine and uric acid were calculated as 98.28 ± 0.45, 94.46 ± 1.77 and 98.57 ± 0.60%, respectively. The voltammetric procedure was also applied to dexamethasone spiked urine samples(5.0 mg/L) and the percent recovery was determined as 95.2% with the relative standard deviations of 3.29%. Conclusion: Sensitive and selective voltammetric method was proposed for the direct determination of dexamethasone. The modified polyglycine-MWCNTs paste electrode enabled the direct determination of dexamethasone in the presence of biological molecules such as ascorbic acid, dopamine and uric acid.
Keywords: Dexamethasone